Potensi Mewujudkan Pondok Pesantren Mahasiswa di Perguruan Tinggi Universitas Jambi Sebagai Penguatan Karakter dan Visi Pendidikan Bangsa - K.A. Rahman; Agung Yusup; Firman Afrian Pratama; Mulyadi (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
In the era of Globalization and Digitalization, it is now easier to spread information, especially religious values. Religious values are integrated in the world of education. There are so many Islamic religious sects spread across Indonesia. However, not all religious sects are recognized for their sanad and the validity of their knowledge. A lot of information about the Islamic religion that is spread cannot be recognized as true because of the lack of reference sources for knowledge and the quality of human resources for teaching staff. Likewise, not all elements of education have a valid (sahih) source of religious knowledge, and not many outputs from education have basic religious values, namely having noble morals. The attitudes, ethics, character and morals of students, especially students at university level, still pay little attention to it. All components only focus on the content and learning values in the form of numbers, without prioritizing educational goals that prioritize morals. As the Messenger of Allah said. "األخالق مكارم ألتمم بعثت إنما " which means actually I (Rasulullah saw.) was sent only to perfect noble morals. This research aims to analyze the potential for realizing Student Islamic Boarding Schools at Jambi University College as Strengthening the Nation's Character and Educational Vision. This research method uses a descriptive library research approach with data analysis techniques by collecting information from various materials such as reference books, relevant research results, articles, notes and various journals related to research. The results of the research show that the potential for realizing Student Islamic Boarding Schools at Jambi University College as Strengthening Character and National Educational Vision is high based on competent teaching backgrounds and students' need for in-depth learning of religious values with clear scientific sources under the guidance of teaching staff. who is competent in the field of Islamic religion at Jambi University.